Organoleptic Properties, Nutritional Value, and Acceptability of Padu Telu with Moringa Leaf Addition - Rahayu Wulandari; I Gde Narda Widiada; Luh Suranadi; Made Darawati (Poltekkes Kemenkes Mataram, 2025)
Background: Padu Telu is the famous fish nugget from Sumbawa. Padu telu is fried and contains fish and coconut, so it has a high protein and fat content. Proteins, antioxidants, and minerals found in moringa leaves (Moringa oleifera) can boost the nutritional content of food items. According to Syahfitri et al. (2022), adding moringa leaves at a rate of 10% of the weight of squid is recommended and significantly affects the color, texture, flavor, and aroma of squid nuggets (p < 0.05).Research Methods: This study aims to evaluate Padu Telu Kelor's (Puriga) acceptability, nutritional value, and organoleptic qualities. The laboratory trial used a one-factor, fully randomized design (RAL) and comprised five doses of moringa leaf therapy (10%, 20%, 30%, 40%, and 50% of the weight of pond fish).Research Result: There was a significant difference (p<0.05) when 20% Moringa leaves were added to the optimal treatment level. Puriga got a 63% approval score in the good category for its nutritional profile, which includes 349 kcal, 7.96% protein, 24.68% fat, and 23.75% carbs.Conclusion: Adding 20% moringa leaves affects color, aroma, taste, and texture (p<0.05). Every 100 grams of Puriga contains 349 kcal of energy, 7.96 grams of protein, 24.68 grams of fat, and 23.75 grams of carbohydrates. Puriga's acceptability was 63% in the good category.